Impact of Neoadjuvant Chemotherapy in Stage II–III Triple Negative Breast Cancer on Eligibility for Breast-conserving Surgery and Breast Conservation Rates. Issue 3 (September 2015) - Golshan, Mehra; Cirrincione, Constance T.; Sikov, William M.; Berry, Donald A.; Jasinski, Sara; Weisberg, Tracey F.; Somlo, George; Hudis, Clifford; Winer, Eric; Ollila, David W.
<x xml:space="preserve">Abstract</x> Objective: To assess the efficacy of neoadjuvant systemic therapy (NST) at increasing the rate of successful breast-conserving therapy (BCT) in triple negative breast cancer. Background: Inducing tumor regression to permit BCT is often cited to support administration of NST. To quantify this benefit, we conducted a surgical companion study to CALGB40603, a randomized phase II, 2×2 factorial trial of neoadjuvant paclitaxel ± carboplatin ± bevacizumab (B) followed by doxorubicin plus cyclophosphamide ± B in stage II–III triple negative breast cancer. Methods: Before and after NST, treating surgeons evaluated BCT candidacy by clinico-radiographic criteria; surgery performed was at surgeon and patient discretion. We measured (1) conversion rates from BCT-ineligible to BCT-eligible, (2) surgical choices in BCT candidates, and (3) rates of successful BCT with tumor-free margins. Results: Four hundred four patients were assessable for surgical outcomes. Two hundred nineteen (54%) were BCT candidates before NST. One hundred ninety-seven (90%) remained BCT candidates after NST, of whom 138 (70%) chose BCT, which was successful in 130 (94%). Of 185 (46%) who were not BCT candidates before NST, 78 (42%) converted to candidates with NST. Of these, 53 (68%) chose BCT with a 91% (48/53) success rate. The overall BCT-eligibility rate rose from 54% to 68% (275/404) with NST. Addition of carboplatin, B, or both increased conversion rates. Conclusions: This is the first study to document prospectively a 42% conversion rate from BCT-ineligible to BCT-eligible, resulting in a 14% absolute increase in BCT eligibility. BCT was successful in 93% of patients who opted for it, but 31% of BCT-eligible patients still chose mastectomy.